Delta Opioid Receptor in Astrocytes Contributes to Neuropathic Cold Pain and Analgesic Tolerance in Female Mice - Reiss, David; Maurin, Hervé; Audouard, Emilie; Martínez-Navarro, Miriam; Xue, Yaping; Herault, Yann; Maldonado, Rafael; Cabañero, David; Gaveriaux-Ruff, Claire (Frontiers in Cellular Neuroscience, 2021)
Background. The delta opioid receptor (DOR) contributes to pain control, and a major challenge is the identification of DOR populations that control pain, analgesia and tolerance. Astrocytes are known as important cells in the pathophysiology of chronic pain, and many studies report an increased prevalence of pain in women. However, the implication of astrocytic DOR in neuropathic pain and analgesia, as well as the influence of sex in this receptor activity, remains unknown. Experimental approach. We developed a novel conditional knockout (cKO) mouse line wherein DOR is deleted in astrocytes (named GFAP-DOR-KO), and investigated neuropathic mechanical allodynia as well as analgesia and analgesic tolerance in mutant male and female mice. Neuropathic cold allodynia was also characterized in mice of both sexes lacking DOR either in astrocytes or constitutively. Results. Neuropathic mechanical allodynia was similar in GFAP-DOR-KO and floxed DOR control mice, and the DOR agonist SNC80 produced analgesia in mutant mice of both sexes. Interestingly, analgesic tolerance developed in cKO males and was abolished in cKO females. Cold neuropathic allodynia was reduced in mice with decreased DOR in astrocytes. By contrast, cold allodynia was exacerbated in full DOR KO females. Conclusions. These findings show that astrocytic DOR has a prominent role for promoting cold allodynia and analgesic tolerance in females, while overall DOR activity was protective. Altogether this suggests that endogenous- and exogenous-mediated DOR activity in astrocytes worsens neuropathic allodynia while DOR activity in other cells attenuates this form of pain. In conclusion, our results show a sex-specific implication of astrocytic DOR in neuropathic pain and analgesic tolerance. These findings open new avenues for developing tailored DOR-mediated analgesic strategies.